2012
DOI: 10.4137/cmo.s6198
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options in Cushing's Disease

Abstract: Endogenous Cushing’s syndrome is a grave disease that requires a multidisciplinary and individualized treatment approach for each patient. Approximately 80% of all patients harbour a corticotroph pituitary adenoma (Cushing’s disease) with excessive secretion of adrenocorticotropin-hormone (ACTH) and, consecutively, cortisol. The goals of treatment include normalization of hormone excess, long-term disease control and the reversal of comorbidities caused by the underlying pathology. The treatment of choice is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 100 publications
(231 reference statements)
0
17
1
Order By: Relevance
“…The data reported by Bolland et al (29) also showed a relatively consistent elevated SMR over four time periods (1960-1980, 1980-1990, 1990-2000, and 2000-present) despite a general shift in pituitarydirected therapy from radiotherapy to TSS, which is at odds with the previously discussed UK data in which the majority of deaths occurred before 1985, before TSS was employed as the standard first-line therapy (36). Nonetheless, early detection and rapid intervention may be key in avoiding long-term sequelae of the disease (41). As CD is a rare disease and, thus, difficult to study, it is hoped that databases such as the ERCUSYN, which now includes more than 500 patients, could become a key resource to further research and aid collaboration (42).…”
Section: Mortality In Patients With CDcontrasting
confidence: 53%
“…The data reported by Bolland et al (29) also showed a relatively consistent elevated SMR over four time periods (1960-1980, 1980-1990, 1990-2000, and 2000-present) despite a general shift in pituitarydirected therapy from radiotherapy to TSS, which is at odds with the previously discussed UK data in which the majority of deaths occurred before 1985, before TSS was employed as the standard first-line therapy (36). Nonetheless, early detection and rapid intervention may be key in avoiding long-term sequelae of the disease (41). As CD is a rare disease and, thus, difficult to study, it is hoped that databases such as the ERCUSYN, which now includes more than 500 patients, could become a key resource to further research and aid collaboration (42).…”
Section: Mortality In Patients With CDcontrasting
confidence: 53%
“…Other agents in this class include aminoglutethimide and etomidate (Table 2). 3,13,[16][17][18][19][20] Steroidogenesis inhibitors are considered adrenal-directed medical therapy because they control cortisol production by directly decreasing adrenal hormone production. Ketoconazole is the most commonly used steroidogenesis inhibitor because of its availability and relatively rapid onset of action.…”
Section: Diagnosis Of Cushing's Syndromementioning
confidence: 99%
“…2 The reasons for failure include large tumor and unidentifiable small microadenoma. Patients with Cushing disease are initially referred to the neurosurgeon for the transsphenoidal surgery.…”
Section: Discussionmentioning
confidence: 99%